2021
DOI: 10.1002/jpen.2242
|View full text |Cite
|
Sign up to set email alerts
|

Physical recovery of COVID‐19 pneumosepsis intensive care survivors compared with non‐COVID pneumosepsis intensive care survivors during post–intensive care hospitalization: The RECOVID retrospective cohort study

Abstract: Background. Coronavirus Disease 2019 pneumosepsis survivors are at a high risk of developing ICU acquired weakness (ICUAW), due to high incidence of acute respiratory distress syndrome and the common need for prolonged invasive ventilation. It remains unknown if regular post-pneumosepsis physical rehabilitation strategies are suitable for this extraordinary patient category.Methods. We retrospectively compared the physical recovery of COVID-19 and non-COVID pneumosepsis ICU survivors between ICU-and hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…In agreement with our results, available studies reported high rates of ICUAW in mechanically ventilated adults with COVID-19. During the pandemic first surge, clinically- assessed ICUAW rates were 52% (n = 26/50) 30 and 100% (n = 35) 31 at ICU discharge, in 2 retrospective studies; and 100% at awakening (n = 110) 32 and 69% (n = 16/23) at the time of extubation 33 in two further prospective studies. Interestingly, these high rates contrast with lower event rates observed in earlier large historical trials of mechanically ventilated adults with non-COVID-19 ARDS ranging 34–36% 34 , 35 consequently, our data raise the question of whether critically ill COVID-19 survivors experience ICU neuromuscular complications more frequently relative to other ARDS populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In agreement with our results, available studies reported high rates of ICUAW in mechanically ventilated adults with COVID-19. During the pandemic first surge, clinically- assessed ICUAW rates were 52% (n = 26/50) 30 and 100% (n = 35) 31 at ICU discharge, in 2 retrospective studies; and 100% at awakening (n = 110) 32 and 69% (n = 16/23) at the time of extubation 33 in two further prospective studies. Interestingly, these high rates contrast with lower event rates observed in earlier large historical trials of mechanically ventilated adults with non-COVID-19 ARDS ranging 34–36% 34 , 35 consequently, our data raise the question of whether critically ill COVID-19 survivors experience ICU neuromuscular complications more frequently relative to other ARDS populations.…”
Section: Discussionmentioning
confidence: 97%
“…Table 2 shows secondary outcomes. Overall FSS-ICU scores at hospital discharge were significantly lower in patients with ICUAW at ICU discharge (26 (19-31) versus 34 (29)(30)(31)(32)(33)(34)(35)). A total of 38 patients (54.3%) were discharged newly gait dependent, out of which, 11 (15.7%) were not able to attempt to walk (FSS walking = 0).…”
Section: Functional Mobility and Gait Dependencementioning
confidence: 89%
“…Patienten, die aufgrund von COVID-19 behandelt wurden, hatten eine geringere Muskelkraft, aber erholten sich rascher als die Vergleichsgruppe. Limitiert ist die Studie aufgrund ihrer geringen Fallzahl (insgesamt nur 56 eingeschlossene Patienten) und auch hinsichtlich ihrer Methodik, da nur retrospektiv und die ICUAW nicht elektrophysiologisch bestätigt wurde [ 40 ].…”
Section: Neuromuskuläre Erkrankungen Nach Covid-19: Was Ist Gesichert?unclassified
“…Moonen i sur. su uspoređivali MRC rezultat i tijek oporavka kod bolesnika koji su razvili ICUAW sa COVID pneumosepsom i ne-COVID bolesnika sa pneumosepsom i došli do zaključka da je ICUAW u COVID bolesnika po otpustu iz bolnice sa manjim MRC rezultatom, ali da se tim bolesnicima mišićna slabost brže oporavlja 46 .…”
Section: Raspravaunclassified